Accounting and Finance for Non-Specialists - Atrill, Peter; McLaney, E. J. (2022)
This edition of 'Accounting and Finance for Non-Specialists' provides comprehensive coverage of the basic concepts and practical applications of financial accounting, management accounting and financial management.
Previous edition: 2019.
Includes index.
Keywords: Accounting; Finance; Finance and Accounting